Characterization of Extra-and Intracelullar from Proliverating Yeast during Tempeh Production - Sutardi Sutardi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2003)
Proliferating yeast species such as Endomycopsis burtonii, Candida diddensiae and Candida iropicalis, produced both extra- and intracellular phytases during tempeh (soaking of soybean) production. The enzymes were isolated from growth media and the cultured yeast. and partially purified by acetone fractionation. Extracellular phytase activities were higher than that of the intracellular enzymes. The extra- and intracellular phytases of E. burtonii., C. diddensiae and C. iropicalis acted over a narrow pH ranging at 3.2 - 4.8 and the maximum activity at temperatures between 45° - 70°C. Estimated Kâ€ž, values for extra- and intracellular phytases from yeast were within the range 0.5 - 3.1.x 10' M. The Vâ€ž,â€žâ€ž values were within the range 0.004 - 0.19 mole P, liberated/min/m1 enzyme for the extra- and intracellular phytases of E. burtonii, C. diddensiae and C. iropicalis. The activation energy for hydrolysis of phytic acid by extra- and intracellular phytases of E. burtonii, C. diddensiae and C. iropicalis were calculated by,the Arrhenius equation being 7,100; 9,100; 13,00, 5,600, 7,100 and 21,700 cal/mole, respectively.